Interpreting environments : tradition, deconstruction, hermeneutics - Mugerauer, Robert (University of Texas Press, 1995)
In this pioneering book, Robert Mugerauer seeks to make deconstruction and hermeneutics understandable and useable for people in the environmental disciplines, including architecture, planning, urban studies, environmental studies, and cultural geography. He chooses case studies to demonstrate the use of each methodology, without advocating any particular one, so that their strategies, assumptions, implications, strengths, and weaknesses become clear. The first case study demonstrates the traditional approach and aims to recover the meaning of Jung's and Wittgenstein's houses by analyzing their historical, intentional contexts. The second case study utilizes the deconstructivist approach to explore Egyptian, French neoclassical, and postmodern attempts to use pyramids to constitute a sense of lasting presence. And the third case study employs hermeneutics to reveal how the American understanding of the natural landscape has evolved from religious to secular to ecological since the nineteenth century.